STUDI TENTANG BENTUK, FUNGSI, DAN MAKNA MONUMEN PERJUANGAN DI MATUR KABUPATEN AGAM - DIAN ADI PRASTIYO, Drs. Erfahmi,M.Sn, Dra. Ernis, M.Pd (Serupa The Journal of Art Education, 2015)
The purpose of this research was to reveal the form, the functions and the meaning on Perjuangan Monument build as historical buildings. The monuments could be used as the source of learning and enrich the knowledge of the current and the next generation to thr memorize what had been done by Indonesian heroes to get and maintain Indonesian Independence implied in Perjuangan Monument. This was a qualitative research which used descriptive analysis approach. The data were collected through observation, interview, stationary and camera. The result of the research indicated that the perjuangan Monument in Matur Kabupaten Agam was build to memorize the struggle of Matur people to get and maintain Indonesian Independence. Behind its building, the monument has a heroic story. The feet, body, and the top of the monument had forms, functions and meaning.Key terms: form, function, meaning, monument, history